ZAKAT, INFAK, DAN SADAQAH SEBAGAI INSTRUMEN PEMBANGUNAN SOSIAL DALAM EKONOMI SYARIAH KONTENPORER - Jailuddin, Syuaib; Sapa, Nasrullah Bin; Misbahuddin (An Nuqud Journal of Islamic Economics, 2025)
The Islamic economic system offers a unique approach to addressing social inequality through a fair wealth distribution mechanism. One of the primary instruments in this system is zakat, infaq, and sadaqah (ZIS), which serve both spiritual and socio-economic functions. This article aims to explain the definitions and distinctions of these three instruments from a sharia economic perspective, while highlighting their role in promoting social justice and strengthening the Muslim community's economy. This research employs a qualitative method with a library research approach, using secondary data obtained from books, academic journals, legal regulations, and relevant institutional documents. The analysis shows that zakat, as a religious obligation, has stricter management mechanisms compared to infaq and sadaqah, which are voluntary. However, all three complement each other in creating a more equitable economic distribution. Together, these instruments serve as vital pillars for developing a sustainable Islamic economic system, especially in the face of current socio-economic challenges